Perancangan dan Pengukuran Kualitas Model User Interface Website Asosiasi Profesi Fotografi Indonesia Sumatera Selatan dengan Metode WebQual - Rike Sucihati; Tata Sutabri (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
One of the uses of advances in information technology is to use a website. To create a website that can meet the needs and maintain user comfort, an easy-to-understand and attractive user interface is needed. On the website of the Indonesian Photography Professional Association, this is a place or gathering place for special photographers in the South Sumatra region. This study aims to develop the website of the Indonesian Professional Photography Association of South Sumatra by designing and measuring the quality of the user interface model. The process of designing this website uses the design thinking method which is expected to focus on solving user problems. Furthermore, from the design results that have been obtained will proceed to the stage of measuring the quality of the user interface model which contains 23 quality measurement variables based on the WebQual approach, which are divided into 4 dimensions, namely usability, information quality, service interaction quality, and user satisfaction get an average score of 3.48 which shows the criteria of very quality. Keywords : User interface, quality, website, design thinking, webqual